A skewed distribution and increased PD-1+Vβ+CD4+/CD8+ T cells in patients with acute myeloid leukemia. Issue 3 (28th May 2019) - Huang, Jingying; Tan, Jiaxiong; Chen, Youchun; Huang, Shuxin; Xu, Ling; Zhang, Yikai; Lu, Yuhong; Yu, Zhi; Chen, Shaohua; Li, Yangqiu
Abstract: The limited application of immunotherapy in acute myeloid leukemia (AML) may be due to poor understanding of the global T cell immune dysfunction in AML. In this study, we analyzed the distribution characteristics of 24 TCR Vβ subfamilies in CD3+, CD4+, and CD8+ T cells in AML patients and healthy controls. The percentage of TCR Vβ subfamily T cells was predominately lower in most AML cases, while it was increased in some cases. TCR Vβ2+T cells were increased in AML, particularly TCR Vβ2+CD4+T cells, which were significantly higher. To further address the immunosuppression in different Vβ subfamilies, we characterized the distribution of program death-1 (PD-1)+T cells in TCR Vβ subfamilies of CD4+ and CD8+T cells. Significantly higher levels of PD-1+Vβ+T cells were found for most Vβ subfamilies in most AML cases. A higher percentage of PD-1+Vβ2+T cells with a high number of Vβ2+T cells was found in all of the CD3+, CD4+, and CD8+ T cell subsets. Moreover, increasing PD-1+Vβ7.2, Vβ8+, Vβ14+, Vβ16+, and Vβ22+CD8+T cells were distributed in the AML-M5 subtype group compared with the AML-M3 group. In addition, higher PD-1+ Vβ5.2+ and PD-1+ Vβ12+CD8+T cells were associated with AML patients who had a poor response to chemotherapy. In conclusion, increased PD-1+Vβ+T cells is a common characteristic of AML, higher PD-1+Vβ2+T cells may be associated with a low antileukemia effect, and higher PD-1+Vβ5.2+ and PD-1+Vβ12+CD8+T cells may be related to poor prognosis in AML. These characteristics may be worth considering as immune biomarkers for clinical outcome in AML. Graphical Abstract: PD-1+Vβ+T cell distributions show higher PD-1+Vβ5.2+ and Vβ12+CD8+T cells, which may be related to a poor prognosis in acute myeloid leukemia.